Climate Change and Vector-Borne Diseases: A Scoping Review on the Ecological and Public Health Impacts (Bangladesh Journal of Medical Science, 2024)
Climate change is increasingly recognized as a significant driver of ecological and public health changes, particularly concerning vectorborne diseases. This scoping review aims to systematically map the current research on the impact of climate change on vector ecology and the subsequent effects on disease transmission dynamics. We conducted a comprehensive literature review across multiple databases to identify critical vectors, such as mosquitoes, ticks, and fleas. We examined how climate variables like temperature, precipitation, and humidity affect their populations, behaviors, and life cycles. Additionally, we explored the shifting geographic distributions of these vectors, investigating how climate change influences their spread and the emergence of diseases such as malaria, dengue, and Lyme disease in new regions. The review highlights the complex and multifaceted interactions between climate change and vector-borne diseases, emphasizing the necessity of understanding these relationships to inform effective public health strategies. Our findings indicate considerable variability in the impacts of climate change across different regions and vector species, underscoring the need for localized studies and tailored interventions. Moreover, significant research gaps were identified, particularly in predictive modeling, long-term surveillance, and the socio-economic impacts of vector-borne diseases exacerbated by climate change. We suggest directions for future research, including the development of integrated climate-health models and enhanced disease surveillance systems, to better anticipate and mitigate the effects of climate change on vector-borne disease transmission. This review underscores the urgency of addressing climate change as a critical component of global health initiatives and the importance of interdisciplinary approaches in tackling this complex issue.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 915-933